2016
DOI: 10.1186/s12931-016-0339-2
|View full text |Cite
|
Sign up to set email alerts
|

Birt-Hogg-Dubé syndrome: a large single family cohort

Abstract: BackgroundBirt-Hogg-Dubé (BHD) syndrome is an autosomal dominant condition characterized by dermatologic lesions, pulmonary manifestations, and renal tumors. The syndrome arises from germline mutations in the folliculin (FLCN) gene. We present findings from the single largest family BHD cohort described to date. Primary objectives were to characterize cystic lung changes on computed tomography (CT) chest scanning and identify features that stratify patients at higher risk of pneumothorax. Secondary objectives … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
31
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(35 citation statements)
references
References 28 publications
2
31
0
Order By: Relevance
“…The multiple pulmonary cysts observed in mutation carriers III-2 and III-3 support this idea. Therefore, it was difficult to calculate the accurate frequency of pulmonary involvement in this family without CT imaging; several previous reports with different sample sizes showed that the number ranges from 70% to 100% (15,(22)(23)(24). Late onset may also play a role in the reported difference in pulmonary involvement.…”
Section: Resultsmentioning
confidence: 84%
“…The multiple pulmonary cysts observed in mutation carriers III-2 and III-3 support this idea. Therefore, it was difficult to calculate the accurate frequency of pulmonary involvement in this family without CT imaging; several previous reports with different sample sizes showed that the number ranges from 70% to 100% (15,(22)(23)(24). Late onset may also play a role in the reported difference in pulmonary involvement.…”
Section: Resultsmentioning
confidence: 84%
“…[2][3][4] Changes in the activity of this protein, presumably with still unconfirmed tumor suppressor activity (via mTOR signaling), may favour the appearance of several of these skin malformations, lungs cysts and renal cancer. [2][3][4][5] Fibrofolliculoma and TD, the hallmarks of BHDS, are clinically indistinguishable and usually appear in individuals in their 20s or 30s and present as asymptomatic multiple, smooth, skin-colored or whitish, dome-shaped papules commonly located on the face (mainly on the nose, forehead and cheeks) although they can also appear on the neck and trunk. [1][2][3]5 Several authors point out that FF and TD (and even acrochorda) may actually represent different stages of evolution within one same lesion.…”
Section: Discussionmentioning
confidence: 99%
“…3 While the age-adjusted risk of pneumothorax is 50 times higher in patients with BHDS than in the general population, lung function is usually normal. 1,[3][4][5][6] Although there is no clear indication for routine CT scanning of the lungs in patients with BHDS, the demonstration of multiple lung cysts strengthens the diagnosis when it is in doubt. Symptomatic patients with lung lesions should have individualized follow-up and all should be reminded of the higher risk of pneumothorax with general anesthesia, during journeys in airplanes or aquatic activities such as diving.…”
Section: 7mentioning
confidence: 99%
See 1 more Smart Citation
“…The data on lung function in BHD are limited to case reports or small series [154, 163, 164]. In 14 patients with baseline data only, the pulmonary function test results were essentially normal with mean spirometric values within the normal range and minimally reduced DLCO [165].…”
Section: Birt-hogg-dubé Syndromementioning
confidence: 99%